2012
DOI: 10.1016/j.genm.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphism in Urinary Angiotensinogen Excretion During Chronic Angiotensin II−Salt Hypertension

Abstract: Background The intrarenal renin–angiotensin system contributes to hypertension by regulating sodium and water reabsorption throughout the nephron. Sex differences in the intrarenal components of the renin–angiotensin system have been involved in the greater incidence of high blood pressure and progression to kidney damage in males than females. Objective This study investigated whether there is a sex difference in the intrarenal gene expression and urinary excretion of angiotensinogen (AGT) during angiotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
(75 reference statements)
3
18
0
Order By: Relevance
“…34,50 Ang II infusion increased renal expression and urinary excretion of AGT in male rats, suggesting that there is an increased AGT availability for conversion to Ang II in kidneys. 13,34,5154 In Dahl-salt sensitive male rats, a high salt diet increased intrarenal AGT expression, BP, proteinuria and glomerolosclerosis, which were prevented by castration and restored by administering testosterone, suggesting that Ang II-induced intrarenal AGT production depends on androgens. 55 Our previous study showing that Ang II stimulated production of testosterone metabolite 6β-OHT via CYP1B1 33 together with the demonstration that the Ang II-induced increase in urinary excretion of AGT was inhibited by Cyp1b1 gene disruption or castration in Cyp1b1 +/+ mice, and that treatment with 6β-OHT restored the increase in urinary excretion of AGT in these mice suggest that 6β-OHT contributes to Ang II- induced intrarenal AGT production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,50 Ang II infusion increased renal expression and urinary excretion of AGT in male rats, suggesting that there is an increased AGT availability for conversion to Ang II in kidneys. 13,34,5154 In Dahl-salt sensitive male rats, a high salt diet increased intrarenal AGT expression, BP, proteinuria and glomerolosclerosis, which were prevented by castration and restored by administering testosterone, suggesting that Ang II-induced intrarenal AGT production depends on androgens. 55 Our previous study showing that Ang II stimulated production of testosterone metabolite 6β-OHT via CYP1B1 33 together with the demonstration that the Ang II-induced increase in urinary excretion of AGT was inhibited by Cyp1b1 gene disruption or castration in Cyp1b1 +/+ mice, and that treatment with 6β-OHT restored the increase in urinary excretion of AGT in these mice suggest that 6β-OHT contributes to Ang II- induced intrarenal AGT production.…”
Section: Discussionmentioning
confidence: 99%
“…410 Testosterone stimulates the expression of renal angiotensinogen (AGT) or urinary excretion of AGT in SHRs and in Ang II-high salt (HS) diet-induced hypertension. 1113 Moreover, castration decreases expression of renal renin and AGT and hepatic AGT in male SHRs. 11,12 Ang II infusion also increases Ang II type 1 receptor (AT1a) expression in male SHRs 14 or alters the Ang II type 2 receptor (AT2) to AT1a receptor balance in kidneys of male SHRs.…”
Section: Introductionmentioning
confidence: 99%
“…Rands et al (2012) reported that male rats display salt-sensitive BP increases during Ang II infusion and the ingestion of HSD while female rats do not. Their findings support our observation of sex differences in salt sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the detailed mechanisms underlying this sex difference remain obscure, they may involve disturbance of the function of the renin-angiotensin-aldosterone system (RAAS) (Rands et al, 2012) and oxidative stress (Sartori-Valinotti et al, 2008). Estrogen deficiency exacerbates experimental ischemic brain damage in rats (Shimada et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our use of the transgenic female Ren2 rat suggests that salt requires excess Ang II and/or aldosterone to precipitate impaired handling of protein. Previous work in this area suggests that increases in proteinuria under conditions of Ang II infusion require 8% of salt intake over 2 weeks [20], while in congenic Ren2:Lewis rats treatment with an agonist of the G protein-coupled estrogen receptor 30 improved proteinuria under a 4%-salt diet [21]. Data from this same study also suggests a higher level of immunostaining of G protein-coupled estrogen receptor 30 in the proximal tubule in this model of excess tissue Ang II, which would support a role for estrogen in Ang II-dependent proximal tubule handling of protein.…”
Section: Discussionmentioning
confidence: 99%